Effects of hippotherapy on motor function of children with cerebral palsy: a systematic review study - Panagiotis Plotas; Angelos Papadopoulos; Evangelia-Maria Apostolelli; Eleni Vlachou; Foteini Gazou; Ioanna Zogopoulou; Ioanna Katsaidoni; Ioanna Panagiotopoulou; Sofia Paraskevi Paparouna; Nikolina Silavou; Katerina Fragkiadaki; Eirini Tsiamaki; et al. (BMC, 2024)
Abstract Cerebral palsy includes a spectrum of neurodevelopmental disorders caused by brain damage, leading to impairment of movement, posture, and balance for a lifetime. There are many therapeutic interventions for cerebral palsy. One of them is hippotherapy, an alternative physical therapy. It is a type of equine-assisted activity and therapy where children with cerebral palsy and motor function skills interact with a horse. We aimed to study the effects of hippotherapy, as an alternative therapy, on the motor function of children with cerebral palsy. We performed a review of the latest literature on hippotherapy and cerebral palsy. The criteria we used were specific keywords, publication date, age of the subjects/studied population, and article type. The outcome of our research resulted in ten relevant studies. The findings demonstrate improvements in various aspects of motor function - more specifically in gross motor function skills, balance, coordination, gait parameters, and muscle strength. Two of ten studies used the Horse-Riding Simulator with significant improvements in postural control in sitting, motor function, and hip abduction range of motion. Hippotherapy can improve motor function skills of children between 2 and 14 years of age with cerebral palsy, affecting their well-being and overall quality of life. It can have a positive effect either as a standalone treatment or as a part of other traditional therapies. Extended research is needed to assess whether hippotherapy may present significant long-term changes in motor skills in children with cerebral palsy.